ChemInform Abstract: A Convenient and General Reduction of Amides to Amines with Low‐Valent Titanium. Issue 16 (22nd April 2014) - Zhang, Tongxin; Zhang, Yan; Zhang, Weixi; Luo, Meiming
Abstract The title method is applied to primary, secondary, and tertiary amides.